Proceedings of the 2016 International Conference on Biomedical and Biological Engineering 2016
DOI: 10.2991/bbe-16.2016.46
|View full text |Cite
|
Sign up to set email alerts
|

Composition Difference of Cholesterol-, Pigment- and Mixed-type Gallstones, and Their Formation Mechanisms

Abstract: Abstract. Objective: The chemical compositions and formation mechanisms of different types of gallstones (cholesterol-, pigment-, and mixed-type) were studied. Methods: The components of gallstones were identified by Fourier transform infrared spectroscopy (FT-IR). The contents of cholesterol, bilirubin and bile acid in gallstones were determined by ultraviolet visible (UV-vis) spectrophotometry. Results: The majority of gallstones in Shenzhen area of China were cholesterol stones, followed by pigment stones. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…This study obtained similar result to the study conducted by Frank et al in 2014, which examined the total clearance in 73 difficult stone subjects who underwent ESWL procedure. 13,14 Lenze et al found 66 subjects (90%) achieved total clearance, three subjects achieved partial clearance, and four subjects (6%) did not achieve total clearance; thus, surgical procedures were performed. Subjects who achieved total clearance underwent ESWL with a shock dose of 3000 shocks, power 60-90 shock/ minute.…”
Section: Discussionmentioning
confidence: 99%
“…This study obtained similar result to the study conducted by Frank et al in 2014, which examined the total clearance in 73 difficult stone subjects who underwent ESWL procedure. 13,14 Lenze et al found 66 subjects (90%) achieved total clearance, three subjects achieved partial clearance, and four subjects (6%) did not achieve total clearance; thus, surgical procedures were performed. Subjects who achieved total clearance underwent ESWL with a shock dose of 3000 shocks, power 60-90 shock/ minute.…”
Section: Discussionmentioning
confidence: 99%